SeaBioTech : from seabed to test-bed: harvesting the potential of marine biodiversity for industrial biotechnology - Edrada-Ebel, RuAngelie; Ævarsson, Arnthor; Polymenakou, Paraskevi; Hentschel, Ute; Carettoni, Daniele; Day, John; Green, David; Hreggviðsson, Guðmundur Óli; Harvey, Linda; McNeil, Brian (Springer, 2018)
SeaBioTech is an EU-FP7 project designed and driven by SMEs to create innovative marine biodiscovery pipelines as a means to convert the potential of marine biotechnology into novel industrial products for the pharmaceutical, cosmetic, aquaculture, functional food and industrial chemistry sectors. To achieve its goals, SeaBioTech brings together leading experts in biology, genomics, natural product chemistry, bioactivity testing, industrial bioprocessing, legal aspects, market analysis and knowledge exchange. SeaBioTech targets novel marine endosymbiotic bacteria from unique and previously untapped habitats, including geothermal intertidal biotopes in Iceland, hydrothermal vent fields and deep-sea oligotrophic basins of the Eastern Mediterranean Sea and underexplored areas of Scottish coasts that are likely to be highly productive sources of new bioactive compounds. This chapter describes the 4 years of activity in the SeaBioTech project, which resulted in a robust, validated workflow suitable for evaluating unexplored activities in marine samples to prioritize potential products for a biotechnological pipeline. An improved integrated methodology involving metagenomics and metabolomics was extensively utilized to prioritize five extremophiles as potential antibiotics, anticancer drugs and novel drugs against metabolic diseases as well as new pharmaceutical excipients to the pipeline. A centralized biobank repository, which included a database of information, was established for future bioprospecting activities. For future marine bioprospecting activities, a harmonized legal position was put together in collaboration with other EU-FP7 blue biotechnology projects.